C12ORF39, a novel secreted protein with a typical amidation processing signal. Issue 1 (17th September 2009) - Wan, Bingbing; Wang, Xin-Rong; Zhou, Yu-Bo; Zhang, Xin; Huo, Keke; Han, Ze-Guang
Abstract : In the present study we describe a novel secreted protein, named C12ORF39 (chromosome 12 open-reading framework 39), which contains a typical amidation/proteolytic processing signal (Gly–Arg–Arg motif). Interestingly, C12ORF39 protein is not hydrolysed, but is a full-length protein without signal peptides. Western blotting indicated that c-Myc-tagged C12ORF39 is secreted into culture medium in transfected HeLa cells. Quantitative RT-PCR (reverse transcription-PCR) analysis revealed that c12orf39 is mainly expressed in placenta and brain. Immunohistochemistry on formalin-fixed paraffin-embedded human term placenta using a rabbit antibody against human C12ORF39 demonstrated that the protein was localized extracellularly, surrounding the trophoblastic cells. In addition, C12ORF39 secretion could be blocked by brefeldin A, suggesting that the secretion of C12ORF39 is dependent on the Golgi apparatus. Furthermore, laser-scanning confocal microscopy also confirmed that the C12ORF39 protein co-localized with the Golgi apparatus. Taken together, although C12ORF39 is not a secreted small peptide, it can also be secreted to play a role in the biological functions of the placenta.